1991
DOI: 10.1093/nar/19.4.789
|View full text |Cite
|
Sign up to set email alerts
|

A sequence motif found in aDrosophilaheterochromatin protein is conserved in animals and plants

Abstract: Modifiers of position-effect-variegation in Drosophila encode proteins that are thought to modify chromatin, rendering it heritably changed in its expressibility. In an attempt to identify similar modifier genes in other species we have utilized a known sequence homology, termed chromo box, between a suppressor of position-effect-variegation, Heterochromatin protein 1 (HP1), and a repressor of homeotic genes, Polycomb (Pc). A PCR generated probe encompassing the HP1 chromo box was used to clone full-length mur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
183
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 272 publications
(190 citation statements)
references
References 43 publications
5
183
0
2
Order By: Relevance
“…As expected, GLP and WIZ were identified as significantly interacting proteins (SAINT Ն 0.9). Additional known G9a-associated proteins include: chromodomain on Y-like 1 (CDYL1) (73,74), which binds methylated H3K9; histone deacetylase 1 (HDAC1) and HDAC2 (75); mesoderm induction early response 1 (MIER1) (76), which represses transcription through recruitment of HDAC1; and chromobox homologs CBX1 (or heterochromatin protein ␤ (HP1␤)) and CBX3 (HP1␥) (77)(78)(79)(80), readers of methylated H3K9. Mass spectrometry analysis by others has shown that many of these proteins interact to form complexes.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, GLP and WIZ were identified as significantly interacting proteins (SAINT Ն 0.9). Additional known G9a-associated proteins include: chromodomain on Y-like 1 (CDYL1) (73,74), which binds methylated H3K9; histone deacetylase 1 (HDAC1) and HDAC2 (75); mesoderm induction early response 1 (MIER1) (76), which represses transcription through recruitment of HDAC1; and chromobox homologs CBX1 (or heterochromatin protein ␤ (HP1␤)) and CBX3 (HP1␥) (77)(78)(79)(80), readers of methylated H3K9. Mass spectrometry analysis by others has shown that many of these proteins interact to form complexes.…”
Section: Discussionmentioning
confidence: 99%
“…A highly conserved 37-amino acid region known as the 'chromo domain' was found at amino acid resides 20-56 in p25. This domain shares > 70% sequence identity with protein in Drosophila and mouse [26]. Recently it was shown that the HP1 chromo domain has chromosome binding activity and that proteins with this domain are recruited to their distinct chromosomal binding sites, probably due to protein-protein interaction [36].…”
Section: Discussionmentioning
confidence: 99%
“…Five of these genes code for histones, two more for chromosomal structural proteins; it is likely that the expression pattern of these genes simply reflects the cycling status of large pre-BII cells. Four genes, however, are involved in transcriptional regulation via structural changes: the modifier-1 protein is involved in heterochromatin formation (Singh et al 1991), whereas SRG-3 is associated with the SWI-SNF complex to modify locus accessibility (Jeon et al 1997). The retinoblastoma-binding proteins RbAp46 and RbAp48 are involved in histone acetylation-dependent transcriptional regulation .…”
Section: Genome Research 101mentioning
confidence: 99%